Impact of task constraints on a 3D visuomotor tracking task in virtual reality - Baillet, Héloïse; Burin-Chu, Simone; Lejeune, Laure; Le Chénéchal, Morgan; Thouvarecq, Régis; Benguigui, Nicolas; Leconte, Pascale (Frontiers in Virtual Reality, 2023)
The aim of the present study was to evaluate the impact of different task constraints on the participants' adaptation when performing a 3D visuomotor tracking task in a virtual environment. Methods: Twenty-three voluntary participants were tested with the HTC Vive Pro Eye VR headset in a task that consisted of tracking a virtual target moving in a cube with an effector controlled with the preferred hand. Participants had to perform 120 trials according to three task constraints (i.e., gain, size, and speed), each performed according to four randomized conditions. The target-effector distance and elbow range of movement were measured.The results showed an increase in the distance to the target when the task constraints were the strongest. In addition, a change in movement kinematics was observed, involving an increase in elbow amplitude as task constraints increased. It also appeared that the depth dimension played a major role in task difficulty and elbow amplitude and coupling in the tracking task.This research is an essential step towards characterizing interactions with a 3D virtual environment and showing how virtual constraints can facilitate arm's involvement in the depth dimension.